2022
DOI: 10.3390/ijerph19116826
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Occupational Stress, Job Satisfaction, and Intention to Leave the Organization among Nurses and Midwives during the COVID-19 Pandemic

Abstract: The current study on the intention to leave the organization among nurses and midwives aligns with the broader direction of research on the consequences of demanding jobs. This is particularly important in the context of the COVID-19 pandemic, which began in 2020 and is ongoing. The aim of the current study was to identify the levels of intention to leave the organization and job satisfaction in a sample of 390 Polish nurses and midwives. A multiple stepwise linear regression was carried out to establish which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 70 publications
3
27
0
Order By: Relevance
“…The studies conducted before the COVID-19 outbreak also showed a relationship between resilience and job satisfaction in nurses. Piotrowski et al (2022), Bernard (2021), Brown et al (2018), Zheng et al (2017) and Hudgins (2015) confirmed the positive effect of resilience on job satisfaction [ 39 43 ]. Studies in the United States [ 41 , 43 , 44 ], Singapore [ 42 ], Turkey [ 45 ] and Pakistan [ 46 ] also showed a positive relationship between nurses’ job satisfaction and resilience because resilience helped nurses to keep their practice effective, overcome their problems, and improve their mental health and well-being.…”
Section: Discussionmentioning
confidence: 96%
“…The studies conducted before the COVID-19 outbreak also showed a relationship between resilience and job satisfaction in nurses. Piotrowski et al (2022), Bernard (2021), Brown et al (2018), Zheng et al (2017) and Hudgins (2015) confirmed the positive effect of resilience on job satisfaction [ 39 43 ]. Studies in the United States [ 41 , 43 , 44 ], Singapore [ 42 ], Turkey [ 45 ] and Pakistan [ 46 ] also showed a positive relationship between nurses’ job satisfaction and resilience because resilience helped nurses to keep their practice effective, overcome their problems, and improve their mental health and well-being.…”
Section: Discussionmentioning
confidence: 96%
“…It might be due to the short‐ and long‐term changes to nurses' work during the COVID‐19 pandemic. During the pandemic, nurses experienced severe work overload, exposure to infection, unpleasant interactions at work, discrimination, despair, and isolation from their families, which exacerbated the existing and widespread workforce stress in the nursing profession (Chen et al, 2021; Piotrowski et al, 2022) and might trigger nurses to leave their job due to stress and fear (Janet Alexis A & Leodoro J, 2021; Khattak et al, 2021; Said & El‐Shafei, 2021). To improve nursing intention to stay, in many countries, medical professionals including nurses working directly with COVID‐19 patients have been given raises, suggesting the financial factor is an important element shaping job satisfaction and intent to stay (Piotrowski et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, nurses experienced severe work overload, exposure to infection, unpleasant interactions at work, discrimination, despair, and isolation from their families, which exacerbated the existing and widespread workforce stress in the nursing profession (Chen et al, 2021; Piotrowski et al, 2022) and might trigger nurses to leave their job due to stress and fear (Janet Alexis A & Leodoro J, 2021; Khattak et al, 2021; Said & El‐Shafei, 2021). To improve nursing intention to stay, in many countries, medical professionals including nurses working directly with COVID‐19 patients have been given raises, suggesting the financial factor is an important element shaping job satisfaction and intent to stay (Piotrowski et al, 2022). However, nursing professional identity concentrates on the meaning of the nursing profession, self‐efficacy, and the impact as a nurse, and it might affect job satisfaction by influencing some components directly but not for the rest, such as salary and workload.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior literature (Piotrowski et al, 2022) has reported that perceived stress has a significant negative impact on nursing job satisfaction, and the higher the perceived stress, the lower the job satisfaction. Failure to deal with stress appropriately can lead to various mental health problems .…”
Section: Perceived Stress Grit and Job Satisfactionmentioning
confidence: 99%